Electrostatic adhesion of polymer particles to a foil electrode. (September 2015) - Ziteng, Li; Praeger, Matthew; Smallwood, Jeremy; Lewin, Paul
Abstract: The SPABRINK EU project requires temporary adhesion of coloured solid "ink" particles to a surface, for later recovery and reuse. This is achieved through the use of dielectrophoretic force under the control of a voltage applied to an interdigitated electrode pattern on the polymer foil. One concern is the ability to hold particles under vibration conditions. In this paper we present an experimental study of the adhesion of 50-300 μm polymer particles to an experimental interdigitated electrode structure on flexible polymer foil. Powder loss as a function of calibrated displacement and applied voltage to the electrodes are presented. This is compared with theoretical results obtained by modelling adhesion using Pohl's equation in terms of an "adhesion factor". Some difficulties in directly comparing experimental and modelling results are discussed.